Construction and validation of a rehabilitation nursing program for fragile elderly - Ana da Conceição Alves Faria; Maria Manuela Ferreira Pereira da Silva Martins; José Alberto Laredo Aguilera; Olga Maria Pimenta Lopes Ribeiro; João Miguel Almeida Ventura da Silva (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To build a rehabilitation nursing program to be implemented in the homes of frail elderly people and validate it by rehabilitation nurses. Methods: This is a qualitative, exploratory study, divided into two stages. The first corresponded to an integrative literature review that supported the construction of the program. The second consisted of the program content validity stage, through a focus group, in May 2021. Results: Nine experts participated in the construction and content validation of the rehabilitation nursing program for frail elderly. Two focus groups were carried out, and the final version of the program included training in life activities and particularly self-care, strength, balance, coordination and joint mobility. Final considerations: The program reached content validity, with a minimum set of characteristics that it must integrate, now requiring application in Primary Health Care for clinical validation.